Belajar dan berkuliner materi aritmetika sosial melalui kegiatan jual beli jajanan tradisional dumbeg - Adi Satrio Ardiansyah; Adistia Nia Safitri; Anisa Firdaus Oktaviani (Mahesa Research Center, 2023)
The assumption that mathematics is a difficult and boring subject result in students' lack of understanding of the mathematics. Lack of teacher creativity in carrying out learning is also considered as one of the causes of these problems. There needs to be innovation in learning mathematics such as the development of innovative teaching materials and in accordance with the characteristics of students. This study aims to develop teaching materials for social arithmetic with Ethnomatematics nuances on Dumbeg objects. Development research with a 4D model that is adjusted to 3D is carried out by paying attention to each stage from define, design, to develop. The data in the study were obtained through interviews, ethnographic notes, and questionnaires which were then analyzed descriptively quantitatively to obtain prototypes of teaching materials that were appropriate, easy to understand, and had a good response to students. The results of the study show that teaching materials are appropriate, easy to understand, and have a good response to students. The feasibility of teaching materials can be seen from the final scores by experts and practitioners of 82.93% and 90.67%, respectively. The readability of teaching materials can be seen from the final score of the readers of 89%. Student responses can be seen from the final score of 95%. Thus, the developed prototype is ready to be implemented in class.